Climate Change in Central Asia Decarbonization, Energy Transition and Climate Policy - Sabyrbekov, Rahat; Overland, Indra; Vakulchuk, Roman (SpringerBriefs in Climate Studies, 2023)
This open access book explores climate change impacts, adaptation, and mitigation in Central Asia and discusses policy options for the Central Asian governments. To address the urgent need for local scholarship on climate change in Central Asia, and in particular the need for more research by social scientists, this book features a wide range of contributions on climate change impacts, adaptation and mitigation in the region. Each chapter makes an important contribution to social science scholarship on climate change and decarbonization in Central Asia. Topics include decarbonization opportunities, carbon pricing instruments, the geo-economics of the energy transition, the relationship between human mobility and climate change. The book thus offers valuable insights for both academics and policymakers.